The European Union's trade disputes: The case of energy sector - Ștefan Cătălin Topliceanu (CES Working Papers, 2023)
Although there are some issues and concerns about the World Trade Organization dispute settlement system, it remains an effective tool for countries to find reasonable solutions for their trading problems. This paper aims to identify the mechanisms of the settlement process between WTO members and to provide a relevant review of the European Union's trade disputes, in particular for energy sector cases. For this purpose, the paper implies a conceptual and descriptive framework and a qualitative approach regarding the EU's trade disputes, especially for energy sector. The results show that the EU is one of the most frequent members in trade disputes, but most of them are concluded. At the same time, most of the cases in the energy sector remain in the consultation phase, the EU being complained by Argentina, Indonesia, Russia, China and Malaysia for sectors related to biodiesel, renewable energy generation and oil palm-based biofuels.
Keywords: 330; energy crisis; WTO dispute settlement; oil trade; Russian fuels; renewable energy